Hydrogen Therapy may be a Novel and Effective Treatment for COPD - Liu, Shu L.; Liu, Kan; Sun, Qaing; Tao, Heng y.; Sun, Xue-Jun (Frontiers in Pharmacology, 2011)
The protective effect of hydrogen (H2) on ROS-induced diseases has been proved by many researches, which demonstrated that through eliminating •OH and •ONOO-, H2 could effectively attenuate lipid and DNA peroxidation, improve cellular antioxidant capacity, and then protect cells against oxidant damage. Most of free radicals in human body are ROS, including O2•-, •OH, H2O2, NO•, •ONOO- and so on. Under normal circumstances cells are able to maintain an adequate homeostasis between the formation and removal of ROS through particular enzymatic pathways or antioxidants. But under some pathological conditions, the balance is disturbed, leading to oxidative stress and various diseases, such as COPD (chronic obstructive pulmonary disease). Studies have shown that ROS played a pivotal role in the development of COPD and some antioxidants were effective in the protection against the damaging effects of oxidative stress. Therefore, we hypothesize that owing to its peculiarity to eliminate toxic ROS, hydrogen therapy may be a novel and effective treatment for COPD.